MALE MEIOSIS AND MORPHOMETRIC ANALYSIS OF ETHNOBOTANICALLY IMPORTANT ALLIUM CAROLINIANUM DC. FROM KINNAUR DISTRICT OF HIMACHAL PRADESH, INDIA - Kamlesh Kumari; Singh Saggoo, Manjit Inder (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: This study is focused on the brief review on the meiosis, ethnobotany and cultivation practices of Allium carolinianum (Family: Alliaceae) from District Kinnaur, Himachal Pradesh. Methods: The local inhabitants were interviews for concerning utilization of this medicinal plant. For meiotic studies the young unopened buds were fixed in carnoy’s fixative, anthers were squashed in 2% acetocarmine. A number of freshly prepared slides were examined for chromosome counts and meiotic abnormalities. Pollen fertility was examined using glyceroacetocarmine (1:1). Photomicrographs were made using Nikon 80i Eclipse Microscope. Results: The present tetraploid chromosome count was in line with the previous report, but the behavioral changes and the medicinal importance of the plant were reported for the first time from the study area. Conclusion: At present, the biodiversity of Kinnaur is threatened by the continuous removal of plant species for various purposes. Hence, the efforts should be made through cultivation practices for the conservation of the medicinal plants. Keywords: Morphometric analysis, Meiosis, Ethnobotany, Cultivation, Allium carolinianum, District Kinnaur.